Analisis Ketersediaan Dan Kebutuhan Ruang Terbuka Hijau (RTH) Di Kawasan Perkotaan Kecamatan Pattallassang Kabupaten Takalar - Ramadan, Awal; Aksa, Kamran; Yahya, Ilham (Journal of Urban Planning Studies, 2023)
The purpose of this research is to identify and to identity derection of fulfilment and need for Green Open Space (RTH) in urban area of Pattallassang District, Takalar Regency. This study uses a quantitative descriptive method to answer factors How the availability and needs of Green Open Space (RTH) in the urban area of Pattallassang District, Takalar Until District the next 20 years by analyzing the availability of space open green. Next to find out how to get directions Fulfillment of Green Open Space (RTH) in urban districts Pattallassang Takalar District used an analysis of the literature sutdy according to the existing condition of thr area. Based on the results of the analysis conducted it was concluded that Space Open Green (RTH) in the urban area of Pattallang is only available 1.79% which is still lacking and 28.21% is still needed Green Open Space (RTH), As for the directives for the fulfillment of Open Spaces Green (RTH) what can be done is that the Government must from now on provide Green Open Space (RTH) land and land bank, Fulfillment of Green Open Space (RTH) can be done in stages for the next 20 years, Fulfilment of Green Open Space City parks, City Forests, District parks, Environmental parks, parks Residents (RW) and Taman Tetangga (RT), and the community are included in fulfilling Green Open Space (RTH).